Lunar transient atmosphere recorded in Chang'e 6 impact glass beads - Ziyan Han; Hejiu Hui; Sen Hu; Zhiyong Xiao; Fanglu Luo; Di Zhang; Yutao Lin; Huicun He; Liang Gao; Yue Zhang; Wenxin Ouyang; Yu Li; et al. (Earth and Planetary Science Letters, 2026)

Assessing soil P and K depletion in unfertilized grassland-crop rotations: A path toward sustainable agriculture - Luiz Gustavo de O. Denardin; Sen Gu; Cornelia Rumpel; François Gastal; Abad Chabbi (Agriculture, Ecosystems & Environment, 2026)

Impact origin of pink spinel in the Chang’e-6 lunar soils - Linxi Li; Guangyuan Yu; Sen Hu; Hejiu Hui; Yi Chen; Qiu-Li Li; Wei Yang; Lihui Jia; Di Zhang; Shitou Wu; Guoqiang Tang; Hao Wang; et al. (Geochimica et Cosmochimica Acta, 2026)

Influence of spring Bering-Okhotsk sea ice on boreal summer intraseasonal oscillation over equatorial central Pacific - Puyu Liu; Yao Ha; Yimin Zhu; Sen Gu; Tianju Wang; Haixia Dai; Yijia Hu; Zhong Zhong (Climate Dynamics, 2026)

Distribution of soil organic carbon in root zones at different distances from the maize basal stem axis and its response to organic materials - Kaixuan Wang; Sen Dou; Baozhao Feng; Boyan Zhang; Yuhan Xia; Dilimulati Yalihong; Yue Gu; Jingmin Yang (Journal of Soils and Sediments, 2026)

A practical adverse-weather maritime vessel detection–tracking framework via an enhanced YOLOv11 detector and BoxMOT association - Weifan Gu; Baohua Guo; Sen Wang; Anthony Sigama; David Bassir (Ocean Engineering, 2026)

Enhanced landslide detection via multi-module deep learning: a morphology-dependent performance analysis approach - Zhengwu Yuan; Sen Kang; Pinglang Kou; Qiang Xu; Xiaobo Luo; Qinchuan Gu; Xinchan Li; Zhao Jin; Chuanhao Pu (Bulletin of Engineering Geology and the Environment, 2026)

Machine learning-based model for evaluating multi-perforation hydraulic fracturing and analysis of fracturing mechanisms - Da Zhao; Zewen Gu; Xiangqing Kong; Sen Wang; Jianlin Liu (Acta Geophysica, 2026)

Multi-level evaluation of sedimentary phosphorus release risk in freshwater water bodies based on dilute-acid extracted phosphorus as indicator - Lanwei Liang; Xin Zhao; Ruilian Guo; Zhenjun Liu; Xiaohan Liu; Xuemei Chen; Yuepeng Yin; Sen Gu; Yang Jiao; Qingman Li (Water Research, 2026)

Precise perception of surface tackiness enabled by a soft single-sensing-element tactile sensor - Ying Yang; Mingwei Gu; Jia-Sen Xie; Xingyu Ma; Yan-Na Lu; Lin Zheng; Jinhui Gu; Junshuai Chen; Yunjie Lu; Denys Makarov; Jin Ge (Science Bulletin, 2026)

Ejecta from Chaffee S Crater in Chang’E-6 Landing Site Constrained by Seifertite-Bearing Norite - Zhan Zhou; Sen Hu; Yubing Gao; Linxi Li; Huicun He; Liang Gao; Mengfan Qiu; Lixin Gu; Xu Tang; Xiaoguang Li; Wei Yang; Yangting Lin; et al. (Journal of Earth Science, 2026)

Mitigation of sulfide stress on eelgrass Zostera marina and Manila clam Ruditapes philippinarum through an eelgrass–clam coculture system - Hang Zhang; Ziyi Xu; Sen Su; Qinxia Yang; Qiyin Tan; Yanlin Wang; Qinyi He; Xuefeng Chen; Weidong Gu; Changzi Ge (Ocean & Coastal Management, 2026)

Duration of high temperature-pressure conditions in impact-induced plumes on the Moon - Xiaoying Liu; Chi Zhang; Zongyu Yue; Lixin Gu; Jing Li; Heng-Ci Tian; Sen Hu; Yangting Lin (Icarus, 2026)

Numerical analysis for landslide deformation and its generated surge waves based on MPM and UAV tilt-photogrammetry modelling technology - Sen Zheng; Chenfei Shao; Chongshi Gu; Yanxin Xu; Zheng Zhu (Natural Hazards, 2026)

Synthesis of artificial humus by hydrothermal carbonization and application to improve soil quality: a review - Yue Gu; Sen Dou; Yutong Song; Dilimulati Yalihong; Yang Jiang; Xiangrong Liu; Jinhua Yue; Song Guan; Dan Guo; Jingmin Yang; Zhongqing Zhang (Environmental Chemistry Letters, 2026)

Delivery of carbonaceous materials to the Moon - Linxi Li; Mengfan Qiu; Sen Hu; Hejiu Hui; Yi Chen; Qiu-Li Li; Wei Yang; Yuyang He; Shitou Wu; Hao Wang; Guoqiang Tang; Di Zhang; et al. (Icarus, 2026)

Microglia Mitochondrial Metabolism in Neurological Diseases - Jin Wang; Yikun Gao; Qing Chen; Xiaoxing Xiong; Sen Miao; Xuemei Chen; Youjia Tang; Lijuan Gu (Molecular Neurobiology, 2026)

Corylifol A ameliorates pancreatic cancer-associated cachexia by targeting TAOK3 in pancreatic cancer cells and targeting TAOK1 in skeletal muscle cells - Ke Yu; Rui-Qin Zhang; Nan Li; Qiong-Sen Wang; Jia Gu; Sai-Yue He; Ying-Qian Wang; Guo-Guo Wang; Xiong-Wen Zhang; Xiao-Dong Guo; Xuan Liu (Toxicology and Applied Pharmacology, 2025)

Lateral dynamic response of bucket foundation in clay considering installation effect - Yufan He; Wenbo Tu; M. Hesham El Naggar; Xiaoqiang Gu; Yaoyu Jia; Lixiang Wei; Sen Li (Ocean Engineering, 2025)

A ternary AuNP/NiFe-LDH/MWCNT heterostructure enhanced electrochemical biomimetic sensor for sensitive detection of enrofloxacin in aquatic foods - Shuanghuan Gu; Sen Wang; Yongju Zhang; Zhixiang Xu; Longhua Xu (Food Chemistry, 2025)

Facile all-in-one detection of nitrofurantoin in feed and milk by magnetic separation assisted differential pulse voltammetry - Xingdong Yang; Wan-yue Zhuang; Sen Zhang; Jie Zou; Aiguo Gu; Qi Wang; Jun-qin Qiao; Hong-zhen Lian (Food Chemistry, 2025)

Corrigendum to “Engineered zwitterionic hydrogel with extreme environment resilience: High ionic conductivity, subzero tolerance, and potential for multimodal sensing and optical applications across devices” [Chem. Eng. J. 510 (2025) 161390/CEJ 161390] - Yan-Na Lu; Kai Mo; Mingwei Gu; Jia-Sen Xie; Ying Yang; Lin Zheng; Xiang-Ru Liu; Yunjie Lu; Jun-Shuai Chen; Jin Ge (Chemical Engineering Journal, 2025)

Kurarinone protects against renal injury and fibrosis after unilateral ureteral obstruction through enhancement of the Nrf-2 signaling pathway - Tiancao Dong; Dongyang Zhao; Sen Jiang; Yi Gu; Chunxue Wang; Qian Yang; Tong Liu; Xiandong Liu (Journal of Molecular Histology, 2025)

Leveraging structural topic modeling to compare “Green Port” research and practice - Hui Zhuang; Yang Chen; Sen Gu; Thierry Vanelslander (Regional Studies in Marine Science, 2025)

The prognostic significance of histopathological growth patterns in liver metastases undergoing surgery: a systematic review and meta-analysis - Xiang-Yu Wang; Bo Zhang; Yin-Chen Gu; Mei Yang; Bao-Rui Tao; Rong-Quan Sun; Yi-Tong Li; Zhen-Mei Chen; Sen-Feng Ying; Chen-He Yi; Yan Geng; Rui Zhang; et al. (Clinical & Experimental Metastasis, 2025)

Highly efficient removal of per- and polyfluoroalkyl substances by extrusion-regenerated aminated polyurethane sponges - Xinhao Wang; Hanyang Chen; Wenran Wang; Xiufang Shen; Jiabao Wang; Sen Chen; Xueru Yu; Chew Tin Lee; Zhanghao Chen; Cheng Gu (Water Research, 2025)

Characteristics of Si Biogeochemical Cycle in Freshwater Riparian Wetlands: A Comprehensive Review - Abdur Rahman; Sen Gu; Qingman Li (Current Pollution Reports, 2025)

Corrigendum to “Discovery of a highly shocked alkali suite clast in the Chang'e-5 lunar soils” [Icarus 429 (2025) 116448] - Mengfan Qiu; Sen Hu; Huicun He; Zongyu Yue; Hejiu Hui; Jialong Hao; Ruiying Li; Sheng Gou; Lixin Gu; Xu Tang; Jinhua Li; Wei Yang; et al. (Icarus, 2025)

Engineered zwitterionic hydrogel with extreme environment resilience: High ionic conductivity, subzero tolerance, and potential for multimodal sensing and optical applications across devices - Yan-Na Lu; Kai Mo; Mingwei Gu; Jia-Sen Xie; Ying Yang; Lin Zheng; Xiang-Ru Liu; Yunjie Lu; Jun-Shuai Chen; Jin Ge (Chemical Engineering Journal, 2025)

Hydrological conditions influence the prediction of soil phosphorus indices on phosphorus leaching in hydromorphic soils - Sen Gu; Rémi Dupas; Antoine Casquin; Wei Liu; Gérard Gruau; Qingman Li; Cornelia Rumpel (Science of The Total Environment, 2025)

Discovery of carbonaceous chondritic fragment in Chang'e-5 regolith samples - Linxi Li; Hejiu Hui; Sen Hu; Qiuli Li; Yi Chen; Wei Yang; Guoqiang Tang; Lihui Jia; Xiaoguang Li; Lixin Gu; Fuyuan Wu (Icarus, 2025)

Discovery of a highly shocked alkali suite clast in the Chang'e-5 lunar soils - Mengfan Qiu; Sen Hu; Huicun He; Zongyu Yue; Hejiu Hui; Jialong Hao; Ruiying Li; Sheng Gou; Lixin Gu; Xu Tang; Jinhua Li; Wei Yang; et al. (Icarus, 2025)

Subaxillary implantation of mesenchymal stem cell spheroids is a novel therapy for myocardial ischemia reperfusion injury - Yihai Liu; Sen Yan; Mingyue Wu; Yuanyuan Xie; Jingyi Sheng; Xuan Sun; Lina Kang; Biao Xu; Ning Gu (Chemical Engineering Journal, 2025)

Sequential oxidation procedures with KMnO4: Component characteristics of labile reducing capacity fractions in anaerobic sediments - Xuemei Chen; Zhijun Li; Songjie Fu; Lanwei Liang; Xiaohan Liu; Fang Hu; Wen Zhang; Yonghong Bi; Yang Jiao; Sen Gu; Qingman Li (Science of The Total Environment, 2024)

Human embryonic stem cell spheroids derived exosomal hsa_circ_0003258 sequestered dual targeting of miR-502-5p on KLF4/NF-κB and GALNT4/P53 to mitigate inflammation and apoptosis in hepatic ischemia reperfusion injury - Ning Wang; Yuwei Zhang; Shuai Zhang; Chuxin Chen; Haibin Wu; Peilin Liao; Shoupei Liu; Sen Chen; Xueyan Zhang; Jinghe Xie; Tingting Guo; Yan Liang; et al. (Chemical Engineering Journal, 2024)

Optimizing radiation capture in machine-harvested cotton: A functional-structural plant modelling approach to chemical vs. manual topping strategies - Shenghao Gu; Shuai Sun; Xuejiao Wang; Sen Wang; Mingfeng Yang; Jie Li; Paerhati Maimaiti; Wopke van der Werf; Jochem B. Evers; Lizhen Zhang (Field Crops Research, 2024)

Degradation of sulfamethazine in coastal aquaculture tailwater by Na2S2O4@iron-electrode electrooxidation combined with ceramic membrane process - Wei Song; Yuning Fang; Hongze Fang; Deming Gu; Xing Du; Sen Xu; Caixia Fu; Yu Zhou; Zhihong Wang (Environmental Pollution, 2024)

Ethanolamine as a biomarker and biomarker-based therapy for diabetic retinopathy in glucose-well-controlled diabetic patients - Guangyi Hu; Liping Gu; Ruonan Wang; Qizhi Jian; Kangjia Lv; Mengxue Xia; Mengyu Lai; Tingting Shen; Jing Hu; Sen Yang; Cunqi Ye; Xiaonan Zhang; et al. (Science Bulletin, 2024)

First discovery of impact-induced vapor deposition of native copper, FeCo alloy and digenite from Chang'e-5 lunar soil - Jing Li; Lixin Gu; Xu Tang; Xiaoying Liu; Sen Hu; Yangting Lin (Icarus, 2024)

Distribution characteristics of reactive silicon in six water bodies in the Yangtze River Basin in China - Xuemei Chen; Lanwei Liang; Songjie Fu; Xu Bao; Sen Gu; Yang Jiao; Fang Hu; Abdur Rahman; Qingman Li (Environmental Research, 2024)

Red mud-based CoFe2O4 activated by ball milling as effective peroxymonosulfate activator for the degradation of lomefloxacin hydrochloride: Preparation & activation, application and degradation mechanism - Junchi Gu; Guangtao Wei; Youlian Zhu; Linye Zhang; Sen Mo; Zhiqiao Yao; Runtao Yang; Baiying Li (Chemical Engineering Journal, 2024)

First classification of iron meteorite fragment preserved in Chang’e-5 lunar soils - Xiaoying Liu; Lixin Gu; Heng-Ci Tian; Jing Li; Xu Tang; Sen Hu; Yangting Lin (Science Bulletin, 2024)

Coupling response of pitch and moonpool water motion of a drilling ship under wave-current excitation - Qi Wei; Jia-Yang Gu; Hong-Guan Lyu; Wei-Min Liu; Xiao-Sen Xu (Ocean Engineering, 2024)

A new approach to extract the upright maize straw from Sentinel-2 satellite imagery using new straw indices - Jingping Zhou; Xiaohe Gu; Cuiling Liu; Wenbiao Wu; Yuchun Pan; Qian Sun; Sen Zhang; Xuzhou Qu (Computers and Electronics in Agriculture, 2024)

Numerical analysis method of equivalent deformation parameters for grouted arch dam abutment fractured rock masses considering scale effects and anisotropy - Chenfei Shao; Yanxin Xu; Jian Chen; Sen Zheng; Hao Gu; Xiangnan Qin (Computers and Geotechnics, 2024)

Long-term fencing can't benefit plant and microbial network stability of alpine meadow and alpine steppe in Three-River-Source National Park - Keyu Chen; Sen Xing; Hailan Shi; Yu Tang; Mingxin Yang; Qiang Gu; Yaoming Li; Jing Zhang; Baoming Ji (Science of The Total Environment, 2023)

A Cross-Seasonal Linkage between Arctic Sea Ice and Eurasian Summertime Temperature Fluctuations - Yanting Liu; Yang Zhang; Sen Gu; Xiu-Qun Yang; Lujun Zhang (Advances in Atmospheric Sciences, 2023)

Experimental study on the influence of fluid motion on hull resistance in stepped moonpool - Qi Wei; Jia-Yang Gu; Hong-Guan Lyu; Wei-Min Liu; Xiao-Sen Xu (Ocean Engineering, 2023)

Hyperspectral estimation of maize (Zea mays L.) yield loss under lodging stress - Qian Sun; Xiaohe Gu; Liping Chen; Xuzhou Qu; Sen Zhang; Jingping Zhou; Yuchun Pan (Field Crops Research, 2023)

Conventional soil test phosphorus failed to accurately predict dissolved phosphorus release in agricultural hydromorphic soils in Brittany, Western France - Sen Gu; Ewan Couic; Gérard Gruau; Antoine Casquin (Geoderma Regional, 2023)

Enhancing wheat Fusarium head blight detection using rotation Yolo wheat detection network and simple spatial attention network - Dong-Yan Zhang; Han-Sen Luo; Tao Cheng; Wei-Feng Li; Xin-Gen Zhou; Wei-Guo; Chun-Yan Gu; Zhihua Diao (Computers and Electronics in Agriculture, 2023)

Bamboo-based magnetic activated carbon for efficient removal of sulfadiazine: Application and adsorption mechanism - Fan Yang; Can Jin; Sen Wang; Yujie Wang; Lu Wei; Longhui Zheng; Haiping Gu; Su Shiung Lam; Mu. Naushad; Cheng Li; Christian Sonne (Chemosphere, 2023)

Effects of gelatinization degree and boiling water kneading on the rheology characteristics of gluten-free oat dough - Yujuan Gu; Xiaojie Qian; Binghua Sun; Xiaoxi Wang; Sen Ma (Food Chemistry, 2023)

Composition, Demographic History, and Population Structures of Trichiurus - Kui-Ching Hsu; Mu-Rong Yi; Sui Gu; Xiong-Bo He; Zhi-Sen Luo; Bin Kang; Hung-Du Lin; Yun-Rong Yan (Frontiers in Marine Science, 2022)
Sequences of the complete mitochondrial cytochrome oxidase subunit I gene were used to identify Trichiurus species and examine their population genetic structure and demographic history along the coast of China. Three Trichiurus species were found. Trichiurus japonicus lives in colder waters along the continental shelves in the China Seas, while Trichiurus nanhaiensis lives warmer waters along continental slopes in the South China Sea, and Trichiurus brevis lives in shallow and warmer waters in the South China Sea. The migrations of these species were mainly associated with feeding and spawning preferences. Two major wintering and spawning grounds in the East China Sea and South China Sea were found. All species showed a lack of population genetic structure resulting from their oceanodromous life cycle (the degree of population substructure index N ST = 0.000–0.149), but the results of approximate Bayesian computational approaches suggested population declines or stabilization and differentiation. The results of the T MRCA (time to the most recent common ancestor) showed that during glaciations, the Yellow Sea and the East China Sea were completely exposed, and the South China Sea acted as a refugium. Thus, the populations of these three species experienced differentiation during glaciations. This study also examined the limitations of Bayesian skyline plot analysis.

First report of leaf spot on Prunus salicina caused by Alternaria alternata in China - Haijiang Long; Sen Yang; Xianhui Yin; Zhibo Zhao; Youhua Long; Juan Fan; Ran Shu; Guifei Gu (Journal of Plant Pathology, 2021)

Thin-layer fine-sand capping of polluted sediments decreases nutrients in overlying water of Wuhan Donghu Lake in China - Yang Jiao; Lei Xu; Qingman Li; Sen Gu (Environmental Science and Pollution Research, 2020)

Challenges of Reducing Phosphorus Based Water Eutrophication in the Agricultural Landscapes of Northwest Europe - Roland Bol; Gerard Gruau; Per-Erik Mellander; Rémi Dupas; Marianne Bechmann; Eva Skarbøvik; Magdalena Bieroza; Faruk Djodjic; Miriam Glendell; Philip Jordan; Bas Van der Grift; Michael Rode; et al. (Frontiers in Marine Science, 2018)

Unexpected spatial stability of water chemistry in headwater stream networks - Benjamin W. Abbott; Gérard Gruau; Jay P. Zarnetske; Florentina Moatar; Lou Barbe; Zahra Thomas; Ophélie Fovet; Tamara Kolbe; Sen Gu; Anne‐Catherine Pierson‐Wickmann; Philippe Davy; Gilles Pinay (Ecology Letters, 2018)
Understanding how water and solutes enter and propagate through freshwater landscapes in the Anthropocene is critical to protecting and restoring aquatic ecosystems and ensuring human water security. However, high hydrochemical variability in headwater streams, where most carbon and nutrients enter river networks, has hindered effective modelling and management. We developed an analytical framework informed by landscape ecology and catchment hydrology to quantify spatiotemporal variability across scales, which we tested in 56 headwater catchments, sampled periodically over 12 years in western France. Unexpectedly, temporal variability in dissolved carbon, nutrients and major ions was preserved moving downstream and spatial patterns of water chemistry were stable on annual to decadal timescales, partly because of synchronous variation in solute concentrations. These findings suggest that while concentration and flux cannot be extrapolated among subcatchments, periodic sampling of headwaters provides valuable information about solute sources and subcatchment resilience to disturbance.

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)